Sistem Pakar Diagnosa Kerusakan Mesin Jahit Menggunakan Metode Certainty Factor - Eka Tresna Ningrum (LPPM STMIK AL MUSLIM, 2022)
Production sewing machines are mechanical or electromechanical equipment that serves to facilitate the sewing process. Likewise in convection, production sewing machines are the main requirement for producing apparel. Convection generally uses Typical and Brother sewing machines. Along with the intense use of sewing machines to produce apparel, it can cause the quality of the components inside to be damaged quickly, requiring technicians to repair them. However, the limited number of technicians caused sewing machine repairs to be delayed. From these problems, an expert system for diagnosing sewing machine damage was made using the certainty factor method. This system was created to help make it easier for users to recognize the early symptoms of sewing machine damage and the solutions. The certainty factor method was chosen to be applied to this system because the results given by this method are in the form of percentages. The percentage is obtained from the calculation between the value of belief or measure of belief (MB) and the value of distrust or measure of disbelief (MD) from a sewing machine expert. The results of the application of the certainty factor method on an expert system for diagnosing sewing machine damage, namely the system can help accelerate users to recognize the symptoms and types of damage. Users obtain a percentage of the confidence level of damage of 85% of the selected symptoms. Keywords: Expert System, Sewing Machine, Certainty Factor Method